Structural and Biophysical Characterization of Murine Rif1 C Terminus Reveals High Specificity for DNA Cruciform Structures - Sukackaite, Rasa (American Society for Biochemistry and Molecular Biology, 2014)
Mammalian Rif1 is a key regulator of DNA replication timing, double-stranded DNA break repair, and replication fork restart. Dissecting the molecular functions of Rif1 is essential to understand how it regulates such diverse processes. However, Rif1 is a large protein that lacks well defined functional domains and is predicted to be largely intrinsically disordered; these features have hampered recombinant expression of Rif1 and subsequent functional characterization. Here we applied ESPRIT (expression of soluble proteins by random incremental truncation), an in vitro evolution-like approach, to identify high yielding soluble fragments encompassing conserved regions I and II (CRI and CRII) at the C-terminal region of murine Rif1. NMR analysis showed CRI to be intrinsically disordered, whereas CRII is partially folded. CRII binds cruciform DNA with high selectivity and micromolar affinity and thus represents a functional DNA binding domain. Mutational analysis revealed an α-helical region of CRII to be important for cruciform DNA binding and identified critical residues. Thus, we present the first structural study of the mammalian Rif1, identifying a domain that directly links its function to DNA binding. The high specificity of Rif1 for cruciform structures is significant given the role of this key protein in regulating origin firing and DNA repair.